Algorytmy sterowania sygnalizacją świetlną w procesie optymalizacji stanu skrzyżowań komunikacyjnych w miastach - Malinowski, Dominik; Labuch, Jolanta (Wydawnictwo Politechniki Łódzkiej, 2022)
This article presents the current state of knowledge on the optimisation of traffic light control systems. It describes the most important and commonly used traffic light control systems and the approaches for determining their optimal solutions. This article also presents the authors’ empirical research on a chosen intersection with particular a focus on time losses in given phase of the cycle. The authors also propose a device which allows for collecting and analysing the parameters of intersections in order to optimise the realtime parameters and to use the phases of this cycle.
Traffic light control algorithms – the optimization of an intersection
Keywords: optimization; intersection status; intelligent transportation system; traffic light control system; optymalizacja; status skrzyżowania; inteligentny system transportowy; system sterowania sygnalizacją świetlną